Islamic Religious Education Teachers' Efforts to Face Social Media Challenges Among Junior High School Students - St. Marwiyah; Alauddin Alauddin; Miftahul Jannah Supriadi (South Sulawesi Education Development (SSED), 2024)
This study aims to observe the phenomenon of social media use among students of SMP Negeri 2 Belopa and the role of Islamic Religious Education teachers in preventing its negative impacts. A qualitative descriptive approach is used using normative pedagogic and theological approaches. Data was obtained through observation, interviews, and documentation at SMP Negeri 2 Belopa for 3 months. The findings showed that social media use hurt student's behaviour and academic performance, such as exposure to negative content and social media addiction. Effective strategies to prevent negative impacts include a personal approach with students, checking students' cellphones, and Islamic religious guidance. However, obstacles such as lack of parental support and environmental influences were also found. As a solution, it is necessary to increase student understanding through integrated education, strengthening cooperation between schools, parents, and students, as well as further studies on the effectiveness of strategies to prevent the negative impact of social media. This step is expected to create an environment that supports healthy and productive use of social media among students of SMP Negeri 2 Belopa.